PROGRAM PENYULUHAN PENGENALAN PERAN SUMBU SEBAGAI PENGIKAT PERKEMBANGAN FISIK KAWASAN BAGI MASYARAKAT PERKOTAAN - Edhi Prasetya; Agus S Sadana; Ashri Prawesti, ST, M.SiP; Diptya Anggita, ST, MT; Swambodo M. Adi, ST, M.Ars.; Margaret Arni (Universitas Pancasila, 2021)
Community service, is the mandate from the Ministry of Education and Culture, to close the distance between the world of education and the daily life of the community, this activity is a manifestation of the implementation of Community Service activities based on the scientific expertise of Architecture. The implementation of this community service activity is in the form of an introduction aimed at various groups in urban communities, conveyed online through Instagram social media. The purpose of this outreach implementation activity is to provide knowledge to the public about the importance of the values ​​of the imaginary axis of the heritage area as the city identity. The implementation of this counseling is related to the material and learning process in the KOKA (Kuliah dan Observasi Kajian Arsitektur) course which has been routinely programmed in each lecture process. On this occasion, which was still in a pandemic condition, the exposure of counseling materials related to the KOKA learning process was transferred in the form of online material exposure through Instagram online social media. As an embodiment, on this occasion the material preparation was carried out based on the direction of the Lecturer Team by involving the student team to produce the online poster. With the implementation of online, the exposure material will continue to be conveyed to the target community automatically since the material is broadcast.